Liquidity windfalls: The consequences of repo rehypothecation - Infante, Sebastian (Journal of Financial Economics, 2019)
This paper presents a model of repo intermediation in which dealers intermediate secured financing between lenders and borrowers using the same collateral. Lenders are insulated from dealers through their repo’s collateral, but borrowers are exposed to dealers through the loss of their collateral. This makes lenders’ repo terms insensitive to dealers’ default, while borrowers’ repo terms are not. The model shows that when repos serve to intermediate collateral, haircuts are negative. This paper explains the difference in haircuts between the bilateral and tri-party repo market and the different run dynamics observed across these markets during the financial crisis.